Role of hydroxamic acids in the resistance of maize, Zea mays L., to western corn rootworm, Diabrotica virgifera virgifera LeConte. - Xie, Yongshou. (University of Ottawa (Canada), 1991)
The role of the maize secondary metabolites, hydroxamic acids, in the interactions of maize, Zea mays L., and western corn rootworm, Diabrotica virgifera virgifera LeConte, was investigated under greenhouse and laboratory conditions. Four compounds found in maize roots, 2,4-dihydroxy-7-methoxy-1,4-benzoxazin-3-(4H)-one(DIMBOA), 2,4-dihydroxy-7,8-dimethoxy-1,4-benzoxazin-3(4H)-one(DIM$\sb2$BOA), 2-hydroxy-7-methoxy-14-benzoxazin-3(4H)-one (HMBOA), and 6-methoxybenzoxazolinone(MBOA), were separated and identified. The highest concentrations of DIMBOA equivalents were found in 4 week old maize root extracts, which overlapped with the time of development of western corn rootworm larvae. Hydroxamic acids and related compounds are concentrated in the cortex of maize roots, which is the feeding site of western corn rootworm larvae. The total concentration of related compounds and the concentration of each individual compound except HMBOA in the complete organ of nodal roots was significantly higher than in any other part of maize roots. The high concentrations of these substances in the cortex of maize root may be relevant to the resistance of maize varieties to subterranean pest insects. Thirty-three inbred maize lines from different latitudinal geographical regions were surveyed for concentrations of hydroxamic acids. All were found to contain four major hydroxamates: DIMBOA, DIM$\sb2$BOA, HMBOA, and MBOA. Differences in concentrations of hydroxamic acids characterized the different geographical groups, and the intermediate temperate region (ITR) group had higher levels of all individual compounds, especially DIMBOA equivalents and the total amount of hydroxamic acids. A positive correlation between concentration of DIMBOA in maize roots and in maize leaves was found. DIMBOA, the major hydroxamic acid present in maize roots, and MBOA, the degradation product of DIMBOA, were studied for their toxic and deterrent effects on western corn rootworm larvae. Exogenously applied DIMBOA and MBOA separately caused mortality in western corn rootworm larvae feeding on fresh corn roots. The deleterious effects of DIMBOA and MBOA on western corn rootworm larvae are possibly due to both feeding deterrence and toxicity. The results indicated that the high DIMBOA line (but not the low DIMBOA line) stressed western corn rootworm larvae to produce inferior adults. ITR 3872 (high DIMBOA) plants showed significantly less damage than NTR-2 Ger. 4042 (low DIMBOA) plants in almost all plant parameters measured. The results suggest that hydroxamic acids may in some instances contribute to the resistance of maize to western corn rootworm larvae. (Abstract shortened by UMI.)
Keywords: Biology, Botany.